2020
DOI: 10.4103/ajns.ajns_185_20
|View full text |Cite
|
Sign up to set email alerts
|

Current role of laser interstitial thermal therapy in the treatment of intracranial tumors

Abstract: Laser interstitial thermal therapy (LITT) is gaining popularity in the treatment of both primary and secondary intracranial tumors. The goal of LITT is to deliver thermal energy in a predictable, controlled, and minimally invasive fashion. It can be particularly valuable in patients with recurrent tumors who, due to previous radiation or surgery, may have a potentially higher risk of wound breakdown or infection with repeat craniotomy. Deep-seated lesions that are often inaccessible through open approaches (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Laser interstitial hyperthermia therapy has shown great potential as a viable treatment option for patients who are prone to or currently experiencing wound complications resulting from previous treatments, based on various research studies. The cumulative evidence indicates that patients who have experienced previous wound complications or are at an elevated risk of impaired wound healing or wound dehiscence may avoid further worse complications by undergoing LITT 2,7,9,11,24–31 . Several studies have shown that patients undergoing LITT after experiencing previous complications have significantly fewer wound complications (1%–10%) than other treatment options 7,10,11,15–17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser interstitial hyperthermia therapy has shown great potential as a viable treatment option for patients who are prone to or currently experiencing wound complications resulting from previous treatments, based on various research studies. The cumulative evidence indicates that patients who have experienced previous wound complications or are at an elevated risk of impaired wound healing or wound dehiscence may avoid further worse complications by undergoing LITT 2,7,9,11,24–31 . Several studies have shown that patients undergoing LITT after experiencing previous complications have significantly fewer wound complications (1%–10%) than other treatment options 7,10,11,15–17 .…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative evidence indicates that patients who have experienced previous wound complications or are at an elevated risk of impaired wound healing or wound dehiscence may avoid further worse complications by undergoing LITT. 2 , 7 , 9 , 11 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Several studies have shown that patients undergoing LITT after experiencing previous complications have significantly fewer wound complications (1%–10%) than other treatment options. 7 , 10 , 11 , 15 , 16 , 17 While a few individuals reported only a few instances of wound complications following LITT, others stated that there were no reported occurrences of wound complications at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first meta-analysis since the 2021 WHO CNS5 guidelines to evaluate the outcomes of LITT as initial therapy in both primary IDH-wildtype GBM and IDH-mutant astrocytoma. Currently, LITT is often used in cases of deep-seated lesions, when there are contraindications to radiotherapy or resection, proximity to eloquent regions, or in cases where patients are particularly vulnerable to wound complications [ 70 , 71 , 72 ]. In the past, LITT has been shown to reduce postoperative complications while maintaining high ablation rates [ 69 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то что теоретическая основа метода разработана в 70-е годы XX века, наиболее крупные серии наблюдений к 2015 г. насчитывали до 20 пациентов. На сегодняшний день этот метод служит дополнительной опцией, применение которой возможно в сочетании с хирургическим лечением, ЛТ и ХТ, но не в качестве самостоятельного метода лечения [26]. Показания к применению методики, по данным литературы, -первичные и рецидивные ЦМ глубинной локализации диаметром 1-3 см, а также ЦМ, не чувствительные к ЛТ [7].…”
Section: Discussionunclassified